Contemporary Understanding of Diagnosis and Treatment of Children with Cystic Fibrosi - A. A. Baranov; L. S. Namazova-Baranova; O. I. Simonova; N. Y. Kashirskaya; E. A. Roslavtseva; Y. V. Gorinova; S. A. Krasovskiy; L. R. Selimzyanova (Union of pediatricians of Russia, 2015)
The issue of contemporary diagnosis and correct management of patients with cystic fibrosis is relevant not only for Russia, but for the entire world. Despite achievements of the contemporary medical science, underdiagnosis of this systemic genetic disorder leading to severe incapacitation and death of pulmonary and heart failure in the vast majority of cases is still observed. The burden induced by this disease is so severe that neonatal screening has been introduced to suspect and detect disease and start pathogenetic treatment capable of stopping or slowing progression of the disease as soon as possible. Apart from the contemporary classification and diagnostic criteria, the article presents treatment goals and components requiring a multidisciplinary approach in detail. Specific attention is given to methods of kinesitherapy, use of antibacterial drugs and enzyme replacement therapy, which primarily determine prognosis of the disease.